Competência ética como recurso de enfrentamento do sofrimento moral em Enfermagem - Schaefer, Rafaela (2016)
The study's objectives were: to seek evidence on ethical situations experienced by nurses in the health services; to identify the coping resources which they use; and to ascertain the role of ethical competence in coping with moral distress. The integrative literature review was used as the method. The search was made in the LILACS, IBECS, MEDLINE, SciELO, CINAHL, PubMed, RCAAP and BDTD databases. A total of 23 studies was selected, based on previously established inclusion and exclusion criteria. The results indicate ethical questions experienced by the nurses in their relations with patients and family members, the team and the health system. Coping resources used by the professionals and implemented by the researchers are described. It may be concluded that the ethical challenges and moral distress are present in the nurses' work context, and the strategies aimed at promoting ethical competence, have positive consequences in coping with, and in reducing, levels of moral distress.